Design, implementation and performance of a controller for uninterruptible solar hot water system - Hasan, Mohammed A.; Arifin, K.; Rahman, Arifur K M Zillur; Azad, AKM Abdul Malek (© 2011 Institute of Electrical and Electronics Engineers Inc., 2016)
This conference paper was presented in the 2011 IEEE 18th International Conference on Industrial Engineering and Engineering Management, IE and EM 2011; Changchun; China; 3 September 2011 through 5 September 2011 [© 2011 Institute of Electrical and Electronics Engineers Inc.] The conference paper's definite version is available at: http://doi.org/10.1109/ICIEEM.2011.6035226